3x+9+2x=3

Simple and best practice solution for 3x+9+2x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9+2x=3 equation:


Simplifying
3x + 9 + 2x = 3

Reorder the terms:
9 + 3x + 2x = 3

Combine like terms: 3x + 2x = 5x
9 + 5x = 3

Solving
9 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 5x = 3 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 3 + -9
5x = 3 + -9

Combine like terms: 3 + -9 = -6
5x = -6

Divide each side by '5'.
x = -1.2

Simplifying
x = -1.2

See similar equations:

| x+8=4x | | 5x+9=3x+4 | | 3(x-9)=6-(x+5) | | (4x+3)+(4x-5)=209 | | 3+8y=8y-3 | | X^3-169x= | | 5h=4h+13 | | x+x+x+3+7+80=180 | | 5h+13=4h+13 | | abs(3x-7)=5 | | 5y=40+y | | 4x^2-15=9 | | 24.5x-4.9(x*x)=29.4 | | 8x^3-512x=0 | | 5=5(x-3)-(x-8) | | 5t-8t+6+4t= | | (6x+5)/2=-10/7+(6x-6)/2 | | 5=(x-3)-(x-8) | | 4x^2+3=7n | | 8a-(5a-7)=1 | | 7x-2=3x-78 | | x+x+3x+7=180 | | -4x+81=-8x+27 | | 4y=7-20 | | x*(3.6-0.6)=4*3.6-4*x | | 6m-2m=60 | | x^2+24x-360=0 | | 4(x-2)=4-(x+6) | | 17=2pir | | 9x-(7x+4)=10 | | x+x-8+x-8(.5)=68 | | 2x*x+7=520 |

Equations solver categories